PRESCRIPTION AUDITING IN REGARD WITH THE PRESCRIPTION PATTERNS IN A TERTIARY CARE TEACHING HOSPITAL - A, Naveen; B, Ramesh; Teki, Siwani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was undertaken to know the prescription patterns and to evaluate the rationality of prescriptions in regard with different parameters in a tertiary care teaching hospital. Methods: This project was a non-interventional, cross-sectional, and observational study conducted at GIMSR Hospital after obtaining permission from Institutional Ethics Committee. A total of 500 prescription forms of the patients who visited the Outpatient Departments of GIMSR hospital, (GITAM University, Visakhapatnam) were recorded and evaluated for different parameters in consonance with the World Health Organization prescribing indicators. Results were analyzed and tabulated using simple statistical measures such as percentages and averages. Results: We collected the data of 500 prescription forms of the patients who visited the hospital during July–August months of the year-2017. In this study, we observed that a total of 1127 drugs were prescribed. Therefore, average number of drugs prescribed per patient was found to be 2.25. Results of prescription profile of the patients results are as follows, drugs prescribed by generic names only in 7.98 % of cases, fixed-dose combinations were used in 15.7%% cases, more than one antibiotic was prescribed in 04% cases, and 87% prescriptions were legible, 73% of prescriptions with complete diagnosis, and only 65.5% prescriptions were complete in terms of dose, route, strength, and frequency and dosage forms. Conclusion: Our study suggests that there is an immense scope of improvement in prescription patterns in the hospital. Majority of drugs (92.07%) were prescribed by the branded names, hence, there is an urgent need for prescription of drugs by generic names. Other parameters such as complete diagnosis and legibility of prescriptions need to be improved.